"I did it wrong, but i know it": Young children's metacognitive knowledge expressions during peer interactions in math activities. (September 2022) - Aydın, Ebru; Dinçer, Çağlayan
Highlights: Preschool children have the capacity to use metacognitive knowledge expressions in math activities. Children state expressions during the measurement activities related to self, other, universals of cognition, and task-specific strategies. Children's metacognitive knowledge is formed by peer interactions. Abstract: Previous studies reveal that children's metacognitive skills make massive progress during the early childhood period. We believe that examining how children use metacognitive skills in the learning process is crucial for shaping future learning experiences. This case study explores how children's metacognitive knowledge emerges through peer interactions in mathematical measurement activities. Sixteen activities based on the dimensions of mathematical measurement skills of length, area, weight, and volume were applied and video recorded. We systematically observed two 5-year-old children in these activities for 10 weeks. A framework of analysis was developed from the results of previous research on children's metacognition. Children's metacognitive knowledge was analyzed in mathematical statements and other variables were also extracted. Using qualitative analysis, this study indicates how children's mathematical thinking skills are reflected in their expressions of metacognitive knowledge during peer interactions. Difficulties in assessing and measuring children's metacognition are also discussed.